Simplify (3x + 5) + (2x - 9) - (4x + 3).

Question

Asked 1/16/2013 9:16:19 AM

Updated 1/17/2013 8:28:58 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey

Rating

0

(3x + 5) + (2x - 9) - (4x + 3)

= 3x + 5 + 2x - 9 - 4x - 3

= x - 7

= 3x + 5 + 2x - 9 - 4x - 3

= x - 7

Added 1/17/2013 8:28:58 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [3/15/2015 1:59:02 PM]

9 - 12n2 + 4n3 - 7n? User: Can you evaluate 9 - 12n2 + 4n3 - 7n? User: What is 9 - 12n2 + 4n3 - 7n? User: Identify the polynomial in a2 + bcd3? **Weegy:** It is binomial. It has 2 terms .............. **User:** Find a - 2b + 3c diminished by a - 2b - 3c + d?
**Weegy:** 6c-d **User:** add 3x2 + 2x - 5 and -4 + 7x2
**Weegy:** 3x^2 - 48 = 0
Add 48 to both sides
3x^2 = 48
Divide both sides by 3
x^2 = 16
x = sqrt (16)
x = 4 or -4
The other solution is 4. (More)

Question

Updated 7/4/2014 5:44:04 PM

3 Answers/Comments

9 - 12n^2 + 4n^3 - 7n

= (n + 1)(4n^2 - 16n + 9)

= (n + 1)(4n^2 - 16n + 9)

Added 7/4/2014 5:41:12 PM

This answer has been confirmed as correct and helpful.

(a - 2b + 3c) - (a - 2b - 3c + d)

= (a - 2b + 3c) + (-a + 2b + 3c - d)

= 6c - d

= (a - 2b + 3c) + (-a + 2b + 3c - d)

= 6c - d

Added 7/4/2014 5:42:35 PM

This answer has been confirmed as correct and helpful.

(3x^2 + 2x - 5) + (-4 + 7x^2)

= 10x^2 + 2x - 9

= 10x^2 + 2x - 9

Added 7/4/2014 5:44:04 PM

This answer has been confirmed as correct and helpful.

32,005,386

questions answered

There are no comments.